2015
DOI: 10.1016/j.intfin.2014.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Reexamining sports-sentiment hypothesis: Microeconomic evidences from Borsa Istanbul

Abstract: This paper examines the impact of international soccer matches on the Turkish stock market using firm-level and sorted-portfolio data. Applying Edmans et al. (2007) estimation method, we found a significant negative loss effect. However, once using panel data analysis as well as modeling spatial and temporal effects explicitly, the sportssentiment effect disappeared. The same conclusions could be made by replacing win (loss) dummies with unexpected win (loss) variables, removing Monday matches, dropping sports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
0
11
1
1
Order By: Relevance
“…The daily returns are computed as the difference in the natural logarithm of the BIST100 index for each of the consecutive trading days. In line with Kaplanski and Levy (2010) and Fung et al (2015) and I run the following regression:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The daily returns are computed as the difference in the natural logarithm of the BIST100 index for each of the consecutive trading days. In line with Kaplanski and Levy (2010) and Fung et al (2015) and I run the following regression:…”
Section: Methodsmentioning
confidence: 99%
“…There is no win effect for any sports. Fung et al (2015) examine the impact of international soccer matches on the Turkish stock market using firm level and sorted portfolio. Using the Edmans et al (2007) estimation method, a significant negative loss effect is found.…”
Section: Introductionmentioning
confidence: 99%
“…A further aspect discussed in the literature concerns the size effect. If investor sentiment exists, a stronger return reaction of stocks with small market capitalization would be expected (among others, Fung et al 2015). This effect may be reasoned by a home bias (French and Poterba 1991).…”
Section: Data Characteristicsmentioning
confidence: 99%
“…Based on these inconsistent results, this paper aims to add empirical evidence to this issue and confirm previous findings. Additionally, we use football clubs from different countries considering that Wilson, Plumley, & Ramchandani (2013), Demir and Danis (2011), Demirhan (2013), Fung, Demir, Lau, & Chan (2015 only focus on single countries (England and Turkey, consecutively) and suggest future studies to use football clubs from other European country leagues. Also, this paper analyzes match results' effects on football clubs not only with abnormal returns but also with trading volume.…”
Section: Introductionmentioning
confidence: 99%